Psychological Dynamics of Sexual Violence Perpetrators: An ITSO-Based Qualitative Case Study in Semarang - Zamroni Zamroni (Journal of Social, Humanity, and Education, 2026)
Purpose: This study explores the psychological dynamics of perpetrators of sexual violence against adult women in Semarang from a perpetrator-focused perspective, which remains underexplored in Indonesian research. Research Methodology: A qualitative case study design framed by the Integrated Theory of Sexual Offending (ITSO) was employed. Three male inmates of the Class I Semarang Penitentiary convicted of sexual offences against adult female victims were selected through purposive sampling and were interviewed using a semi-structured protocol. Data were analyzed thematically through a deductive framework approach based on the four ITSO domains, with validity supported by member checking and by peer debriefing. Results: Four interacting domains emerged: developmental vulnerabilities rooted in adverse childhood experiences; dysfunction of the motivation and emotion system; cognitive distortions within the perception and memory system; and failure of the action-selection and control system. Limitations: The study involved only three participants from a single correctional institution, limiting transferability, and the analysis was conducted by a single coder without inter-rater reliability checks. Conclusions: Sexual offending against adult women reflects an interconnected cycle of psychological dysfunction in which early vulnerability, affect dysregulation, cognitive distortion, and control failure reinforce each other. Contributions: This study represents one of the first applications of the ITSO framework to perpetrators of sexual violence against adult women in an Indonesian correctional setting and provides a basis for developing evidence-based rehabilitation and prevention programs to reduce sexual recidivism.